2005
DOI: 10.1007/s00384-005-0065-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypovolemia after traditional preoperative care in patients undergoing colonic surgery is underrepresented in conventional hemodynamic monitoring

Abstract: Combination of CP with 12 mmHg, head-down position, and infusion of 1,500 ml fluids compensated relative hypovolemia during colonic surgery. With conventional monitoring, intravascular volume status might be underestimated after traditional preoperative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 20 publications
2
17
0
2
Order By: Relevance
“…The results of our study confi rmed the assumption that hypovolemia can be frequently found in patients undergoing major elective surgery (13,22). We also verifi ed high signifi cance of fl ow-related parameters for detection of hypoperfusion abnormalities (23,24,25) while using TED.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of our study confi rmed the assumption that hypovolemia can be frequently found in patients undergoing major elective surgery (13,22). We also verifi ed high signifi cance of fl ow-related parameters for detection of hypoperfusion abnormalities (23,24,25) while using TED.…”
Section: Discussionsupporting
confidence: 82%
“…After introduction to general anesthesia, worsening of global hemodynamic parameters is observed, especially preload, which causes reduction of the CI and parallel elevation of systemic vascular resistance (13). However, traditional parameters such as heart rate (HR), mean arterial pressure (MAP) and central venous pressure (CVP) are often normal (14).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on the PiCCO System were performed during neurosurgery [12], laparoscopic procedures [20] and major abdominal surgery [30 ] and in critically ill patients [13,31]. In all these studies, ITBV was confirmed as a better cardiac preload index when compared with conventional pressure-derived preload indicators (Table 1).…”
Section: Transpulmonary Double Indicator Dilution Techniquementioning
confidence: 90%
“…Die Laparosko pie kommt aber zunehmend bei älteren Patienten mit kardiovaskulären Vorer krankungen zum Einsatz. So konnte auch bei Patienten der ASAKlassen III und IV gezeigt werden, dass eine laparoskopische Cholezystektomie ohne Verschlechte rung der Hämodynamik, der Oxygenati on sowie der Leber und Nierenfunktion durchführbar ist [15] [14]. An hand retrospektiv erhobener Daten wurde bei laparoskopischer Nierenlebendspende eine aggressive (>10 ml/kgKG) mit einer konservativen Flüssigkeitsgabe (<10 ml/ kgKG) verglichen: Bei gleicher Kompli kationsrate in beiden Gruppen fand sich eine signifikante Verkürzung der Kranken hausverweildauer (3 vs. 2 Tage) in der "konservativen" Gruppe.…”
Section: Hämodynamisches Managementunclassified